The impact of a blended multidisciplinary training for the management of obstetric haemorrhage in Mbeya, Tanzania - Mbwele, Bernard; Twaha, Amani; Maksym, Kasia; Caputo, Matthew; Mkenda, Delfina D.; Halpern, Helen; Berney, Sylvia; Kaminyoge, Elias A.; Kaminyoge, Mpoki S.; Kaler, Mandeep; Sobhy, Soha; Hillman, Sara L. (Frontiers in Global Women's Health, 2023)
Background The Maternal Mortality Rate (MMR) in Tanzania is 78 times higher than that of the UK. Obstetric haemorrhage accounts for two-thirds of these deaths in Mbeya, Tanzania. A lack of healthcare providers' (HCPs') competencies has been the key attribute. This study measured the impact on HCP's competencies from a blended training programme on obstetric haemorrhage. Methods A “before and after” cohort study was undertaken with HCPs in 4 hospitals in the Mbeya region of Tanzania between August 2021 and April 2022. A multidisciplinary cohort of 34 HCPs (doctors, nurses, midwives, anaesthetists and radiologists) were enrolled on a blended face-to-face and virtual training course. The training was delivered by a multidisciplinary team (MDT) from London, UK, assisted by local multidisciplinary trainers from Mbeya, Tanzania and covered anaesthetic, obstetrics, haematology and sonographic use. Results There were 33 HCP in the cohort of trainees where 30/33 (90.9%) of HCPs improved their Anaesthesia skills with a mean score improvement of 26% i.e., 0.26 (−0.009 −0.50), 23 HCPs (69.7%) improved obstetric skills 18% i.e., 0.18 (−0.16 to 0.50), 19 (57.6%), (57.6%) improved competences in Haematology 15%.i.e., 0.15 (−0.33 to 0.87), 20 out of 29 HCPs with ultrasound access (68.8%) improved Sonographic skills 13%.i.e., 0.13 (−0.31 to 0.54). All 33 HCPs (100%) presented a combined change with the mean score improvement of difference of 25% i.e., 0.25 (0.05–0.66). The deaths attributed to obstetric haemorrhage, the mortality rate declined from 76/100,000 to 21/100,000 live births. Actual number of deaths due to obstetric haemorrhage declined from 8 before training to 3 after the completion of the training. Conclusion This comprehensive blended training on anaesthetic surgical, haematological, and sonographic management of obstetric haemorrhage delivers a significant positive impact on the detection, management and outcomes of obstetric haemorrhage.